2019
DOI: 10.1002/ps.5622
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bacillus thuringiensis application timing on population dynamics of gypsy moth in Mediterranean cork oak forests

Abstract: BACKGROUND The gypsy moth, Lymantria dispar, is one of the main pests of oak forests worldwide and causes extensive defoliation during its periodic outbreaks. In the Mediterranean region, control of gypsy moth populations in cork oak forests is based on application of Bacillus thuringiensis serovar kurstaki (Btk) formulations. This research investigated the effects of Btk applications carried out in two different population development phases on gypsy moth population dynamics. With this aim, temporal and spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…While a good baculovirus efficacy was achieved in these experiments, larval mortality was significantly lower in comparison with plots treated with Btk, which was confirmed to be a powerful bioinsecticide against gypsy moth [22,23].…”
Section: Discussionmentioning
confidence: 65%
“…While a good baculovirus efficacy was achieved in these experiments, larval mortality was significantly lower in comparison with plots treated with Btk, which was confirmed to be a powerful bioinsecticide against gypsy moth [22,23].…”
Section: Discussionmentioning
confidence: 65%
“…A study by Lentini et al [37] found that outbreaks are generally more frequent in overexploited forests and woodlands (<25% canopy cover rate) than natural ones. Moreover, gypsy moth population dynamics may be further subjected to changes depending on control measures [15]. A study by Mannu et al [15] found a forward shift in abundance peak with early Btk applications during the population growth, leading to postponed outbreak peak by two to three years, whereas Btk applications during the culmination phases were found to be more effective in suppressing gypsy moth populations.…”
Section: Gypsy Moth Population Dynamics (Establishment and Spread) And Potential Impacts Of Female Flightmentioning
confidence: 99%
“…Moreover, outbreaks in established areas are now better regulated in a density-dependent form by two host-specific pathogens, (1) the fungus Entomophaga maimaiga Humber, Shimazu, and Soper (Zygomycetes: Entomophthorales) and (2) a nucleopolyhedrosis virus, LdNPV [13,14]. In addition, aerial application of Bacillus thuringiensis Berliner serovar kurstaki (Btk) is currently the most effective control method to suppress gypsy moth outbreaks in Europe [15]. In areas with established gypsy moth populations, outbreaks generally occur every five to ten years [16] and last between one and three years [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Lymantria dispar population dynamics is described by a typical fluctuation pattern with a starting period of low-density population (latency), after which the pest density increases (progradation), reaches a peak (culmination), and then decreases until returning to low levels (retrogradation) [1,8]. Periodic density fluctuations cause severe outbreaks at regular intervals, which occur from 6 to 13 years, depending on the geographical area and anthropogenic pressure [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%